Tax-and-Spend or Spend-and-Tax? Empirical Evidence from Malaysia - Tan Juat Hong (Asian Academy of Management Journal of Accounting and Finance, 2009)
The paper investigates the causal relationships between government spending and revenue for Malaysia. The study uses annual data, a Johansen cointegration test and an error-correction model. A preliminary test shows that government revenue and expenditure are cointegrated. Empirical results support the spend-and-tax hypothesis. Furthermore, they underscore the fact that fiscal policy may not be effective enough to curb the rising budget deficits over the long term and may even reduce private saving and investment. Extensive expenditure reforms through fiscal synchronisation are suggested.